2017
DOI: 10.1590/2359-3997000000225
|View full text |Cite
|
Sign up to set email alerts
|

Does insulin resistance increase thyroid volume in patients with polycystic ovary syndrome?

Abstract: Objective: To investigate the effect of gonadotropin, sex hormone levels and insulin resistance (IR) on thyroid functions and thyroid volume (TV) in polycystic ovary syndrome (PCOS). Subjects and methods: Sixty nine new diagnosed PCOS patients (age 24.82 ± 6.17) and 56 healthy control female (age 26.69 ± 5.25) were involved to the study. Fasting plasma glucose, lipid profile, insulin, thyroid stimulating hormone (TSH), free thyroxine (fT4), estradiol (E2), luteinizing hormone (LH), follicle stimulating hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Increased TV was reported in patients with IR (25). In the previous study by the authors involving Polycystic Ovary Syndrome patients, significantly increased TV was noted in patients with IR compared to those without IR (TV in insulin-resistant patients was 14.43±2.91, TV in patients without IR was 11.68±2.72, p=0.000) (26). The present study revealed that the frequency of thyroid nodules was higher but not statistically significant (64.4/53.5%, p=0.639), and the mean TV was significantly higher in the NFAI group (13.30±5.95 and 5.99±3.04, respectively, p<0.001).…”
Section: Discussionmentioning
confidence: 79%
“…Increased TV was reported in patients with IR (25). In the previous study by the authors involving Polycystic Ovary Syndrome patients, significantly increased TV was noted in patients with IR compared to those without IR (TV in insulin-resistant patients was 14.43±2.91, TV in patients without IR was 11.68±2.72, p=0.000) (26). The present study revealed that the frequency of thyroid nodules was higher but not statistically significant (64.4/53.5%, p=0.639), and the mean TV was significantly higher in the NFAI group (13.30±5.95 and 5.99±3.04, respectively, p<0.001).…”
Section: Discussionmentioning
confidence: 79%
“…PCOS can be considered a genetic disorder just like T2 DM [27], and it has been occurred in one of each five women within the reproductive age [28,29]. On the other hand, it was found that high Estradiol levels may affect the thyroid cells [30]. In hyperandrogenemia, Testosterone level measurement is very important [31].…”
Section: Resultsmentioning
confidence: 99%
“…In human medicine, cysts are benign and require no special intervention. Nevertheless, a relationship has been described between insulin resistance syndrome and the presence of thyroid cysts and thyroid volume, with a prevalence of 45% of thyroid cysts in people with severe insulin resistance [ 37 , 38 ]. In human, small cysts (< 3 mm diameter) may spontaneously disappear [ 39 ].…”
Section: Discussionmentioning
confidence: 99%